PENGARUH PROFITABILITAS, LEVERAGE, DAN PERSISTENSI LABA PADA EARNING RESPONSE COEFFICIENT - Sudarmayasa, Made Ariadi; Ratna Sari, Maria Mediatrix (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.08.TAHUN.2024DO - 10.24843/EEB.2024.v13.i08.p05, 2024)
This study aims to determine the effect of profitability, leverage and earnings persistence on the Earnings Response Coefficient (ERC). The research was conducted at consumer non-cyclicals sector companies on the Indonesia Stock Exchange (IDX) for the 2018-2021 period. The population of this study is all consumer non-cyclicals companies registered on the IDX in 2018-2021. Data was collected through non-participant observation methods. Non-probability sampling method with purposive sampling technique was used to collect samples, which consisted of 39 companies and 156 observation samples. Multiple linear regression analysis test was used to perform data analysis. The results show that profitability affects ERC negatively, while leverage and earnings persistence do not affect ERC.